Co‐benefits between biodiversity and hydrological ecosystem services allow an efficient conservation planning proposal for the Riviera Maya, Mexico - Juan Alberto Aguilar‐Sánchez; Melanie Kolb (Conservation Science and Practice)
Abstract Including biodiversity and ecosystem services (ES) spatial priorities in reserve design through quantitative methods known as systematic conservation planning has been proposed to identify spatial solutions that achieve both elements in a spatially efficient manner. The aim of this study is to evaluate the differences between priority sites for biodiversity and hydrological ecosystem services (HES) and to identify opportunities for co‐benefits that allow an efficient conservation planning proposal, using as a case study the Riviera Maya, Mexico. The results confirm the following: (1) biodiversity and HES priority sites have different spatial patterns, sharing only 24% of priority sites; (2) HES priority sites achieve a high percentage (95%) of biodiversity conservation targets, showing that they can potentially be used for biodiversity representation; and (3) integrating HES and biodiversity into one model is more efficient to represent conservation targets than considering both elements individually (46% vs. 66% of the study area). These results reflect the lack of irreplaceable sites for biodiversity conservation, and as <8% of the study area is currently covered by protected areas, this means that there are numerous opportunities to align cobenefits of biodiversity and HES conservation actions.